Competition of Definition and Pictorial Illustration for Dictionary Users' Attention: An Eye-Tracking Study. (23rd February 2017) - Lew, Robert; Kaźmierczak, Rafał; Tomczak, Ewa; Leszkowicz, Mateusz
Abstract: Dictionaries sometimes include pictorial illustrations to complement verbal explanation. The present study examines the question of how verbal and pictorial elements within an entry compete for dictionary users' attention, and how this competition affects meaning extraction and retention. The study employs eye-tracking technology to analyse the gaze patterns of Polish learners of English consulting illustrated monolingual English learner dictionary entries. In addition, success in identifying and remembering meaning based on illustrated items is assessed and related to eye-tracking data.